Digital Game as A Media to Increase Cognitive Intelligence of 13-18 Years Old Teenagersã€€ - Edbert, Ivan Sebastian; Tsaniya, Devita Azka; Constantino, Bernico; Riandy, Geary; Aulia, Alvina; Nadia, Nadia (Engineering, MAthematics and Computer Science Journal (EMACS), 2024)
Nowadays, Cognitive Intelligence plays an essential role especially on making decisions. The growth of digital media makes public thinks that video games are addictive. They think that video games are addictive and damaging. Games are design to refresh, challenge and help people to train their problem solving. In this research, the researcher explored the cognitive development of teenagers aged 13-18 with a puzzle-based digital game. Participants were 15 students studying in junior and senior high school. Participants were given three tests: pre-test and post-test by IQ test and a Game Engagement Questionnaire (GEQ) to explore the game's engagement from the participants' perspective. The average of Pre-Test is 113.2, while the Post-Test is 118.33. This Show that after playing the games it increases the IQ of the students. The researcher also discovered that many factors could influence the outcome of participant IQ. The GEQ shows that the participants agreed that some of the puzzle-based game might be a good or bad influence on them. Keywords: Cognitive Intelligence; Digital Games, Formal Operational Game-based Learning, Jean Piaget's Theory